2018
DOI: 10.1159/000491913
|View full text |Cite
|
Sign up to set email alerts
|

Non-Esterified Fatty Acids Over-Activate the TLR2/4-NF-Κb Signaling Pathway to Increase Inflammatory Cytokine Synthesis in Neutrophils from Ketotic Cows

Abstract: Background/Aims: Dairy cows with clinical ketosis display a negative energy balance and high blood concentrations of non-esterified fatty acids (NEFAs), the latter of which is an important pathological factor of ketosis in cows. The aims of this study were to investigate the inflammatory status of ketotic cows and to determine whether and through what underlying mechanism high levels of NEFAs induce an inflammatory response. Methods: Proinflammatory factors and the nuclear factor kappa B (NF-κB) signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…Recently, Zhang and coworkers (2018) have shown that ketotic cows with low glucose and high NEFA concentrations have higher blood concentrations of inflammatory cytokines. Those authors related the phenomenon to an overactivation of toll-like receptor 2/4-mediated NF-κB pathway signaling in polymorphonuclear neutrophils as a cause for increasing inflammation in cows suffering from ketosis (Zhang et al, 2018). In the present study, ketosis was treated as soon as ketone bodies were detected in the urine, and mean BHB levels were under the cutoff value for ketosis (p.p.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, Zhang and coworkers (2018) have shown that ketotic cows with low glucose and high NEFA concentrations have higher blood concentrations of inflammatory cytokines. Those authors related the phenomenon to an overactivation of toll-like receptor 2/4-mediated NF-κB pathway signaling in polymorphonuclear neutrophils as a cause for increasing inflammation in cows suffering from ketosis (Zhang et al, 2018). In the present study, ketosis was treated as soon as ketone bodies were detected in the urine, and mean BHB levels were under the cutoff value for ketosis (p.p.…”
Section: Discussionmentioning
confidence: 68%
“…Elevated NEFA concentrations have been linked to severity of inflammation during coliform mastitis [ 25 , 47 ]. Elevated pre-FM treatment circulating NEFAs among cows that died in this study, when compared to those that survived, may be indicative of an exacerbated inflammatory response since circulating NEFAs and COX-2 enzyme can be increased via upregulation of Toll-like receptor (TLR) signaling [ 21 , 28 , 30 ]. Increased production of pro-inflammatory eicosanoids through the COX pathway can then lead to further adipose mobilization and NEFA release, creating a positive feedback cycle [ 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, mediators not only act on localized mammary tissues, but also can have systemic effects, leading to increased mobilization of adipose tissue and increased circulating non-esterified fatty acids (NEFAs) [ 6 , 13 , 23 , 24 , 25 , 26 , 27 ]. Prolonged elevated NEFAs results in systemically increased production of cytokines, adhesion molecules, eicosanoids through increased expression of COX-2 and free radicals, such as reactive oxygen species (ROS) [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the toll‐like receptor‐4 (TLR4) inhibitor C‐34 (10 μ m ; Zhang et al . 2018) blocked the effect of LPS on NG neurons (Fig. 6, F (2,65) = 5.31, P < 0.01; one‐way ANOVA followed by Tukey's multiple comparison test).…”
Section: Resultsmentioning
confidence: 90%